Nonlinear Galerkin Method and Crank-Nicolson Method for Viscous Incompressible Flow (Journal of Computational Mathematics, 1999)
In this article we discuss a new full discrete scheme for the numerical solution of the Navier-Stokes equations modeling viscous incompressible flow. This scheme consists of nonlinear Galerkin method using mixed finite elements and Crank-Nicolson method. Next, we provide the second-order convergence accuracy of numerical solution corresponding to this scheme. Compared with the usual Galerkin scheme, this scheme can save a large amount of computational time under the same convergence accuracy. \u00a0